Implementasi Pengembangan Anak Usia Dini Holistik Integratif (PAUD HI) di KB dan TK Islam Silmi Samarinda - Inna Zakiyah; Mujahidah; Sunanik (PT. Berkah Smart Academica, 2024)
This school has started implementing a holistic integrative early childhood development program (PAUD HI) ranging from education, health, nutrition and care, care, protection and welfare services. The aim of the research was to find out the implementation of holistic integrative early childhood development and to find out the supporting and inhibiting factors in the Silmi Samarinda Islamic KB and Kindergarten. This type of qualitative research with a phenomenological approach. Data collection techniques used are observation, interviews, and documentation. The data validity technique used is triangulation. The process of data analysis is data condensation, data presentation, and drawing conclusions. The results of the research are that the Silmi Samarinda Islamic KB and Kindergarten have carried out five services namely education, health, nutrition and care, parenting, protection and welfare services properly. This can be seen from the fulfillment of the components and indicators of the success of PAUD HI, although some indicators are not optimal in care and protection services. The supporting factors are collaboration with the education office, health centers and parents, IGTKI, adequate infrastructure and using appropriate learning approaches and methods, careful preparation, agreement with children, understanding, caring, parenting, communication with parents who well, there are teacher pickets, operational funding assistance and accepting children with special needs. The inhibiting factors are the lack of preparation, participation and busyness of parents, unfavorable weather, inadequate outdoor games and lack of cooperation with the police and the population and civil registration services.